Reviewer - Souleles, Nicos (My University, 2026)
Higher Education Studies (HES) is a double-blind peer-reviewed international journal dedicated to promoting scholarly exchange among teachers and researchers in the field of post-secondary education. The journal is published quarterly in both print and online versions by the Canadian Center of Science and Education. https://www.ccsenet.org/journal/index.php/hes/about